Platinum complexes featuring terminally bound Ga(+) and In(+) ions. - Aldridge, S (2006)
(Chemical Equation Presented) Alone at the apex: The first metal complexes with Ga+ or In+ cations as terminally bound ligands have recently been synthesized. Structural and computational studies suggest a Lewis acid/base Pt-Ga interaction for [GaPt(GaCp*)4]+ (1; Pt blue, Ga violet, C gray; ArF = C6H3-(CF 3)2-3,5). The Group 13 cation therefore functions as an acceptor ligand, with significant components of both σ and π symmetry contributing to the Pt-Ga linkage. © 2006 Wiley-VCH Verlag GmbH and Co. KGaA.